COMMUNICATION OF JAMINAN KESEHATAN NASIONAL POLICY (JKN) BY BADAN PENYELENGGARA JAMINAN SOSIAL IN KOTA KEFAMENANU DISTRICT NORTH CENTRAL TIMOR DISTRICT - Tola, Kristoforus; Fritantus, Yohanes; Rembu, Yoakim (Universitas Negeri Gorontalo, 2024)
Communication is very important in a policy. When communication in a policy does not work well, it is difficult to implement the policy. This research method is descriptive qualitative. The research results show that clarity of purpose, completeness, conciseness and concise content, feedback, empathy, changing messages according to audience needs, various communication channels, and effective use of informal communication channels. As a result of the research, it can be concluded that the communication of the National Health Insurance Policy (JKN) by the Social Security Administering Body (BPJS) for Health in the City District, North Central Timor Regency (TTU) has been going well but is not yet optimal. This occurs as a result of the first, clarity of objectives where The message conveyed by the organizers was not clear, which made the public unable to differentiate between the JKN and BPJS Health programs. Second, is completeness, where the message conveyed by the organizers is incomplete, which causes the public to not understand the JKN program. Third, brevity where you don't know the main indicators that you need to know about the JKN program. Fourth, feedback where the community will provide feedback when they experience problems or difficulties when wanting to use the BPJS Health card, not during the communication or socialization process for the JKN program. Fifth, sharing communication channels where the organizers have prepared communication channels to disseminate information about the JKN program but the public prefers to go directly to the BPJS Health office to get services or submit complaints.